Cause-specific infant mortality in Copenhagen 1861–1911 explored using individual level data - Louise Ludvigsen; Barbara Revuelta-Eugercios; Anne Løkke (Historical Life Course Studies)
This study explores cause-specific infant mortality in Copenhagen between 1861 and 1911, using newly available individual-level data from The Copenhagen Burial Register, as part of a larger comparative project within the SHiP network (Studying the history of Health in Port Cities). The aim is to determine the dominant cause of death patterns for infants and to explore how the ICD10h coding system performs with the Danish individual level-historical causes of death. The results show that in Copenhagen, infant mortality began a distinct decline during the period of study (1861–1911), but the city experienced only very few changes in the cause of death pattern. While a transition from symptomatic to more specific causes of death took place over time, the largest killers overall were the water-food borne and airborne diseases, with a respectively summer and winter peak. The airborne and water-food borne diseases were mainly dominant amongst the post-neonates, whose mortality made up an increasingly larger share of infant deaths. Finally, the results show that although coding the Danish causes of death to the ICD10h has proven successful, more attention needs to be paid to different uses of the same cause of death by different nations, such as the case of atrophy.